2009
DOI: 10.1097/brs.0b013e3181978fee
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional C-Arm Computed Tomography-Guided Sacroplasty for the Treatment of Sacral Body Fracture

Abstract: 3-dimensional C-arm CT-guided sacroplasty is a safe, practical, and effective solution to treatment of sacral body fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Inevitably spinal trauma will be part of this evolution; however, to our knowledge, only one study has reported on this clinical application. Ishikawa et al described O-arm assisted cervical pedicle screw insertion in a cohort that included six patients with traumatic injuries.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Inevitably spinal trauma will be part of this evolution; however, to our knowledge, only one study has reported on this clinical application. Ishikawa et al described O-arm assisted cervical pedicle screw insertion in a cohort that included six patients with traumatic injuries.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3][4][5][6][7] Despite this, little has been written on the emerging role of O-arm in the surgical management of patients with acute spinal trauma.…”
Section: Introductionmentioning
confidence: 98%
“…Later, Garant established the details of the technique and described the sacroplasty applications (9). Many studies on this subject were published in the recent years, and details like the technique used (short-or long-axis technique) (9,20), imaging technique used (fluoroscopy or CT) (3,(14)(15)(16)19,21,26), amount of cement injected and presence or absence of balloon use were reported. However, the risk-benefit ratio is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sacroplasty, which can be defined as sacral vertebroplasty and/or kyfoplasty, was first reported in 2000 for osteolytic tumors (6,17), and was described in detail by Garant in 2002 (9). This procedure is performed under CT (14)(15)(16)19,21,26) or C-arm fluoroscopy (11). Rather good results are reported in both osteoporotic (4,7,8,18,28) and tumor-related (10,24,26,29) sacral fractures.…”
Section: Introductionmentioning
confidence: 99%
“…A study found some authors recommend CT-guided sacroplasty (15,20) instead of sacroplasty under C-arm fluoroscopy. Although the advantages gained by CT-guided sacroplasty were emphasized by some authors (5,11,16,17,20,25), real-time fluoroscopic imaging is needed for visualizing cement leakage. Moreover, the use of CT is associated with higher radiation exposure for both patients and operating room staff (11,19).…”
Section: Discussionmentioning
confidence: 99%